Reconfigurable metamaterial structure for 5G beam tilting antenna applications - F. Esmail, Bashar A.; A. Majid, Huda; Dahlan, Samsul Haimi; Zainal Abidin, Zuhairiah; Himdi, Mohamed; Dewan, Raimi; A. Rahim, Mohamad K.; Ashyap, Adel Y. I. (Taylor and Francis, 2020)
In this paper, we propose a metamaterial (MTM) structure with a reconfigurable property designed to operate at the millimetre-wave (mm-wave) spectrum. Four switches are used to achieve the reconfigurable property of the MTM with two configurations. These two configurations exhibit different refractive indices, which used to guide the radiation beam of the antenna to the desired direction. The proposed planar dipole antenna operates at the 5th generation (5G) band of 28 GHz. The electromagnetic (EM) rays of the proposed antenna pass through different MTM configurations with different phases, subsequently results in the tilting of the radiation beam toward MTM configuration of high refractive index. Simulated and measured results of the proposed antenna loaded by MTM demonstrate that the radiation beam is tilted by angles of +34° and −31° in the E-plane depending on the arrangement of two MTM configurations onto the antenna substrate. Furthermore, the gain is improved by 1.7 and 1.5 dB for positive and negative tilting angles, respectively. The reflection coefficients of the antenna with MTM are kept below −10 dB at 28 GHz.